Sodium-ion battery positive electrode material and preparation method thereof
Preparing sodium ion battery positive electrode materials by using iron source and layered oxide precursor by-products and carbon materials, simplifies the process flow, reduces costs and improves performance, solves the problem of high-purity raw materials, and achieves environmental protection and economical Improvement of sex.
Patent Information
- Application Number
- CN202411084642.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-08
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-08-08
AI Technical Summary
In the preparation process of existing sodium ion battery positive electrode materials, the demand for high purity sodium and iron sources leads to high costs and limited production capacity, and the process is complex, affecting environmental protection and economicality.
Using iron source and layered oxide precursor by-products with sodium sulfate, as well as carbon materials as raw materials, granulation and sintering are carried out after purification treatment to prepare sodium ferrosulfate positive electrode material containing a variety of metal ions, simplifying the process and Improve waste utilization.
It reduces raw materials and production costs, improves waste utilization, reduces energy consumption and environmental protection costs, improves the rate performance and circulation performance of the positive electrode material of sodium ion battery, and improves its economic and environmental friendliness.
Smart Images

Figure FT_1 
Figure FT_2 
Figure SMS_1
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of sodium ion batteries, and in particular to a sodium ion battery positive electrode material and a preparation method thereof. Background Art
[0002] Sodium ferric sulfate positive electrode material has the remarkable characteristics of low cost, high voltage, long cycle, and high safety performance. It is suitable for application scenarios such as electric vehicles and energy storage. In the current mainstream sodium ferric sulfate synthesis process, the raw materials used are mostly ferrous sulfate and sodium sulfate powder. In order to ensure the product quality of sodium ferric sulfate positive electrode material, the ferrous sulfate and sodium sulfate used are both battery grade. They are produced through chemical synthesis methods to ensure the purity of ferrous sulfate and sodium sulfate, which increases the overall preparation cost of sodium ferric sulfate and limits its production capacity. Summary of the invention
[0003] In view of the problems existing in the above-mentioned prior art, the present application provides a sodium ion battery positive electrode material and a preparation method, and the technical solution is as follows: On the one hand, the present application provides a sodium ion battery positive electrode material, the sodium ion battery positive electrode material comprising sodium ferric sulfate, a carbon material and a plurality of metal ions, the carbon material is dispersed between the sodium ferric sulfate, and the metal ions are doped in the crystal structure of the sodium ferric sulfate; The sodium ion battery positive electrode material is prepared using an iron source, a layered oxide precursor byproduct having sodium sulfate, and a carbon material as raw materials; the layered oxide precursor byproduct includes metal ions, and the metal ions include Ni 2+ 、Co 2+ and Mn 4+ At least two of the .
[0004] Further, the iron source is a titanium dioxide byproduct having ferrous sulfate heptahydrate, the titanium dioxide byproduct includes metal ions, the titanium dioxide byproduct and / or the layered oxide precursor byproduct include metal ions, and the metal ions include Ni 2+ Mg 2+ 、Co 2+ and Mn 4+ ; The chemical formula of the sodium ion battery positive electrode material is Na x Fe y Ni a Co b Mn c Mg d (SO 4 ) z @C, where 1≤x / y≤2, (a+b+c+d) / y≤0.1.
[0005] Furthermore, the sodium ion battery positive electrode material is obtained by performing a first purification treatment on a titanium dioxide byproduct to obtain a first purified solution, performing a second purification treatment on a layered oxide precursor byproduct to obtain a second purified solution, mixing the first purified solution, the second purified solution and a carbon material, drying them, and granulating and sintering them; The first purification treatment can remove insoluble substances in the titanium dioxide byproduct, and the first purification solution includes ferrous sulfate heptahydrate and a plurality of soluble metal ions, wherein the soluble metal ions include Ni 2+ Mg 2+ and Mn 4+ At least two of the following; The second purification treatment can remove ammonia nitrogen in the layered oxide precursor byproduct; the second purification solution includes sodium sulfate and a plurality of soluble metal ions, wherein the soluble metal ions include Ni 2+ 、Co 2+ and Mn 4+ At least two of the .
[0006] Furthermore, the first purified solution and the second purified solution are mixed according to a preset x / y value between the sodium element and the iron element by measuring the iron content and the sodium content in the first purified solution, measuring the sodium content in the second purified solution; wherein 1.2≤x / y≤1.8.
[0007] On the other hand, the present application also provides a method for preparing a positive electrode material for a sodium ion battery, wherein the positive electrode material for a sodium ion battery is prepared using an iron source, a layered oxide precursor byproduct having sodium sulfate, and a carbon material as raw materials; the layered oxide precursor byproduct includes metal ions, and the metal ions include Ni 2+ 、Co 2+ and Mn 4+ At least two of the following; The sodium ion battery positive electrode material comprises sodium ferric sulfate, a carbon material and a plurality of metal ions, wherein the carbon material is dispersed among the sodium ferric sulfate, and the metal ions are doped in the crystal structure of the sodium ferric sulfate.
[0008] Furthermore, the iron source is a titanium dioxide byproduct having ferrous sulfate heptahydrate, and the titanium dioxide byproduct includes metal ions, and the metal ions include Ni 2+ Mg 2+ , and Mn 4+ At least two of the above; the sodium ion battery positive electrode material prepared by using an iron source, a layered oxide precursor byproduct having sodium sulfate and a carbon material as raw materials comprises: The titanium dioxide byproduct is subjected to a first purification treatment to obtain a first purified solution; the first purification treatment can remove insoluble substances in the titanium dioxide byproduct, and the first purified solution includes ferrous sulfate heptahydrate and a plurality of soluble metal ions, wherein the soluble metal ions include Ni 2+ Mg 2+ and Mn 4+ At least two of the following; The layered oxide precursor byproduct is subjected to a second purification treatment to obtain a second purified solution; the second purification treatment can remove ammonia nitrogen in the layered oxide precursor byproduct, and the second purified solution includes sodium sulfate and a plurality of soluble metal ions, wherein the soluble metal ions include Ni 2+ 、Co 2+ and Mn 4+ At least two of the following; Mixing and drying the first purified solution, the second purified solution and the carbon material to obtain a positive electrode material precursor; Granulating the positive electrode material precursor to obtain a precursor pressed material; The precursor pressed material is sintered and crushed to obtain the sodium ion battery positive electrode material.
[0009] Furthermore, the first purification process of the titanium dioxide byproduct to obtain a first purified solution comprises: Dissolving the titanium dioxide byproduct in deionized water and dispersing iron powder in the deionized water to obtain a first initial solution; The sodium hydroxide solution and the first initial solution are mixed until the pH of the first initial solution reaches a first target pH, and filtered to obtain a filtrate; the first target pH is 4.5-5; the titanium dioxide byproduct also includes Ti 2+ , in the case of the first target pH, the Ti in the first initial solution 2+ A precipitation reaction occurs to form an insoluble titanium precipitate; Sulfuric acid, an antioxidant and the filtrate are mixed until the pH of the filtrate reaches a second target pH to obtain the first purified solution; the second target pH is 2 to 3.5.
[0010] Furthermore, the titanium dioxide byproduct is subjected to a first purification treatment to obtain a first purified solution that satisfies at least one of the following characteristics: The insoluble matter of the titanium dioxide by-product includes titanium dioxide, and the mass proportion of the titanium dioxide in the titanium dioxide by-product is less than the first mass proportion, and the first mass proportion is 0.7% to 1.3%; The mass proportion of the multiple soluble metal ions of the first purified solution in the titanium dioxide by-product is less than the second mass proportion, and the second mass proportion is 0.7% to 1.3%; The concentration of ferrous sulfate heptahydrate in the first initial solution is 50 g / L to 150 g / L; The mass percentage between the iron powder and the ferrous sulfate heptahydrate is 0.1% to 1%; The pH of the sodium hydroxide solution is 10 to 13; The antioxidant comprises at least one of ascorbic acid, oxalic acid and citric acid; The mass percentage between the antioxidant and the ferrous sulfate heptahydrate is 0.1% to 3%.
[0011] Further, the step of performing a second purification treatment on the layered oxide precursor byproduct to obtain a second purified solution comprises: Deaminate the layered oxide precursor byproduct to obtain a second initial solution; Sulfuric acid and the second initial solution are mixed until the pH of the second initial solution reaches a third target pH, thereby obtaining the second purified solution; the third target pH is 6.7 to 7.0.
[0012] Furthermore, the layered oxide precursor byproduct is subjected to a second purification treatment to obtain a second purified solution that satisfies at least one of the following characteristics: The pH of the layered oxide precursor byproduct is greater than 12; The concentration of sodium sulfate in the layered oxide precursor byproduct is 50 g / L to 200 g / L; The ammonia nitrogen content in the layered oxide precursor byproduct is 5 g / L to 10 g / L; The content of the plurality of soluble metal ions of the second purified solution in the layered oxide precursor by-product is 75 mg / L to 130 mg / L.
[0013] On the other hand, the present application also provides a sodium ion battery, comprising the sodium ion battery positive electrode material as described in any of the above items, or comprising the sodium ion battery positive electrode material prepared by the preparation method of the sodium ion battery positive electrode material as described in any of the above items.
[0014] Implementing this application has the following beneficial effects: The sodium ion battery positive electrode material is prepared by using an iron source, a layered oxide precursor byproduct having sodium sulfate and multiple metal ions, and a carbon material as raw materials. The process waste is used as a sodium source to prepare the sodium ion battery positive electrode material, thereby realizing a preparation process flow directly from byproducts to the sodium ion battery positive electrode material, improving waste utilization rate, and compared with the preparation process requiring a high-purity sodium source in the traditional process, simplifying the production process of the sodium ion battery positive electrode material, reducing the raw material cost and the production cost of the sodium ion battery positive electrode material, and also greatly saving the energy consumption and environmental protection cost caused by processing the layered oxide precursor byproducts and other process wastes, reducing carbon emissions in the production environment, and improving the economy and environmental friendliness of the sodium ion battery positive electrode material and its preparation process.
[0015] The layered oxide precursor byproduct of the present application has Ni 2+ ,Co 2+ The prepared sodium ion battery positive electrode material contains metal ions Ni 2+ ,Co 2+ , where Ni 2+ Due to the presence of Ni 2+ / Ni 3+ Redox couple, which can provide capacity during the charge and discharge process, Co 2+ The charge transfer impedance can be effectively reduced, thereby improving the rate performance of the positive electrode material of the sodium ion battery. The capacity of the sodium ion battery prepared using the positive electrode material of the present application is improved, and has good rate performance.
[0016] At the same time, the preparation method does not require additional doping of metal ions, which not only simplifies a process but also saves the raw material cost of metal ions. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] In order to more clearly illustrate the technical solution of the present application, the following is a brief introduction to the drawings used in the embodiments, wherein the same components are represented by the same reference numerals. Obviously, the drawings described below are only some embodiments of the present application, and for those of ordinary skill in the art, other drawings can be obtained based on these drawings without creative work.
[0018] Figure 1 A flow chart of a method for preparing a positive electrode material for a sodium ion battery provided in Example 1 of the present application; Figure 2 This is a comparison chart of the rate performance of the sodium ion battery positive electrode materials provided in Example 1 and Comparative Example 1 of the present application. DETAILED DESCRIPTION
[0019] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments, and therefore cannot be understood as limiting the present application. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0020] It should be noted that in the description of the present application, for the following defined terms, unless a different definition is given in the claims or elsewhere in this specification, these definitions should be applied. All numerical values, whether or not explicitly indicated, are defined herein as being modified by the term "about". The term "about" generally refers to a numerical range that a person of ordinary skill in the art would consider to be equivalent to the stated value to produce substantially the same properties, functions, results, etc. A numerical range indicated by a low value and a high value is defined to include all numerical values included in the numerical range and all subranges included in the numerical range.
[0021] It should be noted that the terms "first", "second", etc. in the specification, claims and drawings of the present application are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequential order. It should be understood that the objects used in this way can be interchanged where appropriate, so that the embodiments of the present application can be implemented in a sequence other than the following diagrams or the following descriptions. In addition, the terms "including" and "having" and any of their variations are intended to cover non-exclusive inclusions, for example, the process, method, system, product comprising a series of steps or units is not necessarily limited to those steps or units clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, or products.
[0022] The embodiment of the present application provides a sodium ion battery positive electrode material, which includes sodium ferric sulfate, a carbon material and a plurality of metal ions, wherein the carbon material is dispersed between the sodium ferric sulfate, and the metal ions are doped in the crystal structure of the sodium ferric sulfate, that is, the metal ions are filled in the crystal structure of the sodium ferric sulfate; and the sodium ion battery positive electrode material is prepared by using an iron source, a layered oxide precursor byproduct having sodium sulfate and a carbon material as raw materials, the layered oxide precursor byproduct includes metal ions, and the metal ions include Ni 2+ 、Co 2+ and Mn 4+ At least two of the .
[0023] Among them, sodium sulfate is a by-product of the lithium battery\sodium battery layered oxide positive electrode material precursor industry. Theoretically, about 1.5 tons of sodium sulfate will be produced during the synthesis of one ton of layered oxide positive electrode material precursor, and all of this sodium sulfate is present in the waste liquid of the precursor synthesis. The present application uses industrial waste as a sodium source to prepare sodium ion battery positive electrode materials, realizes a preparation process flow directly from by-products to sodium ion battery positive electrode materials, improves waste utilization, and simplifies the production process of the sodium ion battery positive electrode material compared to the traditional process that requires a high-purity sodium source, reduces the cost of raw materials and the production cost of the sodium ion battery positive electrode material, and also greatly saves the energy consumption and environmental protection costs caused by processing the layered oxide precursor by-products and other process wastes, reduces carbon emissions in the production environment, and improves the economy and environmental friendliness of the sodium ion battery positive electrode material and its preparation process.
[0024] The layered oxide precursor byproduct of the present application has Ni 2+ ,Co 2+ The prepared sodium ion battery positive electrode material contains metal ions Ni 2+ ,Co 2+ , where Ni 2+ Due to the presence of Ni 2+ / Ni 3+ Redox couple, which can provide capacity during the charge and discharge process, Co 2+ The charge transfer impedance can be effectively reduced, thereby improving the rate performance of the positive electrode material of the sodium ion battery. The capacity of the sodium ion battery prepared using the positive electrode material of the present application is improved, and has good rate performance.
[0025] At the same time, the preparation method does not require additional doping of metal ions, which not only simplifies a process but also saves the raw material cost of metal ions.
[0026] Specifically, in some exemplary embodiments, the iron source is a titanium dioxide byproduct having ferrous sulfate heptahydrate, and at least one of the titanium dioxide byproduct and the layered oxide precursor byproduct includes a metal ion, and the metal ion includes Ni 2+ Mg 2+ 、Co 2+ and Mn 4+ .
[0027] Among them, ferrous sulfate heptahydrate is the largest by-product in the titanium dioxide industry. Theoretically, the production of one ton of titanium dioxide will produce 3.5 to 4 tons of titanium dioxide by-products. The present application further uses industrial waste as an iron source to prepare sodium ion battery positive electrode materials, realizing a preparation process flow directly from by-products to sodium ion battery positive electrode materials, further improving waste utilization. Compared with the preparation process that requires a high-purity iron source in traditional processes, the production process of the sodium ion battery positive electrode material is further simplified, the cost of raw materials and the production cost of the sodium ion battery positive electrode material are reduced, and the energy consumption and environmental protection costs brought about by the treatment of titanium dioxide by-products and other process wastes are greatly saved, reducing carbon emissions in the production environment, and improving the economy and environmental friendliness of the sodium ion battery positive electrode material and its preparation process.
[0028] At least one of the titanium dioxide byproduct and / or the layered oxide precursor of the present invention includes metal ions, and the metal ions include Ni 2+ Mg 2+ 、Co 2+ and Mn 4+ The prepared sodium ion battery positive electrode material also includes Ni 2+ Mg 2+ 、Co 2+ and Mn 4+ .
[0029] Among them, Ni 2+ Existence of Ni 2+ / Ni 3+ The redox pair can also provide capacity during the charge and discharge process, which can further increase the capacity of the positive electrode material of the sodium ion battery to a certain extent; Mg 2+ Doping in the crystal structure of sodium iron sulfate can make the sodium ion battery positive electrode material obtain a smaller particle size morphology, increase the contact area between the electrode sheet with the sodium ion battery positive electrode material and the electrolyte in the sodium ion battery, further accelerate the charge transfer between the electrode sheet and the electrolyte interface, and Mg 2+ It can also play a supporting role in the lattice, preventing the crystal structure in the positive electrode material of the sodium ion battery from collapsing during the cycle, thereby improving the cycle stability of the positive electrode material of the sodium ion battery; Co 2+ It can effectively reduce the charge transfer impedance and improve the rate performance of the positive electrode material of the sodium ion battery; Mn 4+It does not change price and does not participate in the charging and discharging process, but it can also improve the structural stability of the positive electrode material of the sodium ion battery; by doping a variety of metal ions in the crystal structure of sodium ferric sulfate, it can effectively improve the rate performance and cycle performance of the positive electrode material of the sodium ion battery, and make up for the performance degradation that may be caused by insufficient purity of raw materials, so that the sodium ion battery positive electrode material prepared with titanium dioxide by-products and layered oxide precursor by-products as part of the raw materials has a performance comparable to that of the sodium ferric sulfate positive electrode material made from high-purity raw materials.
[0030] Specifically, in some exemplary embodiments, the metal ions of the titanium dioxide byproduct include Ni 2+ Mg 2+ , and Mn 4+ In other exemplary embodiments, the metal ions of the layered oxide precursor byproducts include Ni 2+ 、Co 2+ and Mn 4+ At least two of the .
[0031] In some exemplary embodiments, the titanium dioxide byproduct includes metal ions, and the metal ions in the titanium dioxide byproduct include Mg 2+ and Mn 4+ In other exemplary embodiments, the layered oxide precursor byproduct includes metal ions, and the metal ions in the layered oxide precursor byproduct include Ni 2+ 、Co 2+ and Mn 4+ .
[0032] In other exemplary embodiments, the titanium dioxide byproduct includes metal ions, and the metal ions in the titanium dioxide byproduct include Ni 2+ Mg 2+ and Mn 4+ , and the layered oxide precursor byproduct includes metal ions, and the metal ions in the layered oxide precursor byproduct include Ni 2+ 、Co 2+ and Mn 4+ .
[0033] Specifically, the chemical formula of the positive electrode material of the sodium ion battery is Na x Fe y Ni a Co b Mn c Mg d (SO 4 ) z@C, where 1≤x / y≤2, (a+b+c+d) / y≤0.1; it can be understood that the value of x / y can be any value between 1 and 2, and the value of (a+b+c+d) / y can be any value less than or equal to 0.1; illustratively, the value of x / y can be 1, 1.1, 1.2, 1.5, 1.7, 1.9, 2, etc.; the value of (a+b+c+d) / y can be 0.1, 0.08, 0.05, 0.03, 0.01, 0.008, 0.0 0.4, 0.002, etc.; in this way, the sodium ion battery positive electrode material can have a good specific capacity, and the rate performance and cycle performance of the sodium ion battery positive electrode material are improved; further, in some exemplary embodiments, 1.2≤x / y≤1.8; in some preferred embodiments, 1.3≤x / y≤1.7, (a+b+c+d) / y≤0.05, which is beneficial to further improve the specific capacity of the sodium ion battery positive electrode material, and improve the rate performance and cycle performance of the sodium ion battery positive electrode material.
[0034] Specifically, the positive electrode material of the sodium ion battery is obtained by subjecting the titanium dioxide byproduct to a first purification treatment to obtain a first purified solution, subjecting the layered oxide precursor byproduct to a second purification treatment to obtain a second purified solution, mixing the first purified solution, the second purified solution and the carbon material, drying them, and granulating and sintering them.
[0035] The titanium dioxide by-product is a solid waste material containing insoluble substances, including insoluble titanium dioxide and insoluble impurities (e.g., dust, particles), etc. The first purification treatment can remove the insoluble substances in the titanium dioxide by-product, and the various metal ions in the titanium dioxide by-product include various soluble metal ions. During the first purification treatment, the various metal ions can be at least partially dissolved, so that after the first purification treatment, the first purified solution includes ferrous sulfate heptahydrate and various soluble metal ions, and the soluble metal ions in the first purified solution include Ni 2+ Mg 2+ and Mn 4+ At least two of the above can be doped into the crystal structure of sodium iron sulfate in the subsequent preparation process to improve the performance of the positive electrode material of the sodium ion battery.
[0036] The layered oxide precursor byproduct is a liquid waste in the form of a solution. The layered oxide precursor byproduct contains ammonia nitrogen and a small amount of metal ions. Ammonia nitrogen (NH 3 -N) refers to the free ammonia (NH 3 ) and ammonium salts (NH 4+) in the form of nitrogen, the second purification treatment can remove ammonia nitrogen in the layered oxide precursor byproduct, so that after the second purification treatment, the second purification solution includes sodium sulfate and a plurality of soluble metal ions, and the soluble metal ions in the second purification solution include Ni 2+ 、Co 2+ and Mn 4+ At least two of the above can be doped into the crystal structure of sodium iron sulfate in the subsequent preparation process to improve the performance of the positive electrode material of the sodium ion battery; in addition, it should be noted that the metal ions and / or soluble metal ions in this application refer to the metal ions other than Na + and Fe 2+ The impurity metal ions are relatively small in content and are used to dope the crystal structure of sodium iron sulfate. Other metal ions may also exist in the titanium dioxide by-product and the layered oxide precursor by-product, such as Ca 2+ and Al 3+ Etc., may remain in the positive electrode material of the sodium ion battery after preparation, but their effect on the performance of the positive electrode material of the sodium ion battery is small and can be ignored.
[0037] In this way, there is no need to purify each by-product to an extremely high purity to produce a sodium ion battery positive electrode material with relatively good performance, saving the cost of purifying and recycling industrial waste, improving waste utilization, and reducing pollution. At the same time, using industrial waste as raw materials to prepare sodium ion battery positive electrode materials can also simplify the production process and reduce the production cost of sodium ion battery positive electrode materials.
[0038] Specifically, the first purified solution and the second purified solution are mixed according to a preset x / y value between the sodium element and the iron element by measuring the iron content and the sodium content in the first purified solution, measuring the sodium content in the second purified solution; wherein 1.2≤x / y≤1.8; this is conducive to improving the accuracy of the proportion of each component in the positive electrode material of the sodium ion battery and effectively improving the performance of the positive electrode material of the sodium ion battery.
[0039] Specifically, the carbon material includes at least one of graphite, graphene, carbon black, single-walled carbon nanotubes and multi-walled carbon nanotubes, has good electrical conductivity, can effectively enhance the electrical conductivity between ions, reduce the risk of battery polarization in a sodium ion battery having the sodium ion battery positive electrode material, inhibit grain growth, shorten the transmission path of sodium ions in the sodium ion battery positive electrode material, improve the sodium ion transmission efficiency, and greatly improve the conductivity of the sodium ion battery positive electrode material.
[0040] Specifically, the mass proportion of carbon material in the positive electrode material of the sodium ion battery is 0.5% to 10%; it can be understood that the mass proportion of carbon material in the positive electrode material of the sodium ion battery can be any point value between 0.5% and 10%; illustratively, the mass proportion of carbon material in the positive electrode material of the sodium ion battery can be 0.5%, 0.7%, 1.0%, 1.5%, 2.0%, 3.0%, 5.0%, 8.0%, 10% and the like; in this way, the carbon material has good dispersion uniformity in the positive electrode material of the sodium ion battery, which can improve the conductivity, conductivity uniformity and electrochemical performance of the positive electrode material of the sodium ion battery.
[0041] On the other hand, the present application also provides a method for preparing a positive electrode material for a sodium ion battery, wherein an iron source, a layered oxide precursor byproduct having sodium sulfate, and a carbon material are used as raw materials to prepare a positive electrode material for a sodium ion battery; the layered oxide precursor byproduct includes metal ions, and the metal ions include Ni 2+ 、Co 2+ and Mn 4+ At least two of the above; the positive electrode material of the sodium ion battery includes sodium ferric sulfate, a carbon material and a plurality of metal ions, the carbon material is dispersed between the sodium ferric sulfate, and the metal ions are doped in the crystal structure of the sodium ferric sulfate.
[0042] Specifically, in some exemplary embodiments, the iron source is a titanium dioxide byproduct having ferrous sulfate heptahydrate, and a sodium ion battery positive electrode material is prepared using the titanium dioxide byproduct having ferrous sulfate heptahydrate, a layered oxide precursor byproduct having sodium sulfate, and a carbon material as raw materials; wherein at least one of the titanium dioxide byproduct and / or the layered oxide precursor byproduct includes a metal ion, and the metal ion includes Ni 2+ Mg 2+ 、Co 2+ and Mn 4+ .
[0043] Among them, titanium dioxide by-products refer to by-products generated in the process of producing titanium dioxide, mainly including ferrous sulfate heptahydrate and acid solution; in the process of producing lithium battery / sodium battery layered oxide positive electrode materials, the lithium battery / sodium battery layered oxide positive electrode material precursor will be formed, and then the final lithium battery / sodium battery layered oxide positive electrode material is obtained based on the lithium battery / sodium battery layered oxide positive electrode material precursor; the layered oxide precursor by-product refers to the waste liquid after co-precipitation and filtration of the lithium battery / sodium battery layered oxide positive electrode material precursor in the process of producing lithium battery / sodium battery layered oxide positive electrode materials, and the waste liquid contains sodium sulfate; based on the layered oxide precursor by-product and the titanium dioxide by-product as raw materials, the sodium ion battery positive electrode material can be prepared, which not only realizes the reuse of various by-products, saves the energy consumption and environmental protection costs brought by the treatment of by-products, but also simplifies the preparation process of the sodium ion battery positive electrode material, reduces the preparation difficulty and preparation cost of the sodium ion battery positive electrode material, and at the same time can also make the prepared sodium ion battery positive electrode material have good performance.
[0044] Moreover, under the large output of existing chemical production, the preparation of sodium ion battery positive electrode materials based on the titanium dioxide by-product and the layered oxide precursor by-product can provide sufficient iron and sodium sources for the preparation of sodium ion battery positive electrode materials, solving the problem of limited production capacity of sodium ion battery positive electrode materials.
[0045] Specifically, when the iron source is a titanium dioxide byproduct having ferrous sulfate heptahydrate, the sodium ion battery positive electrode material prepared by using the iron source, the layered oxide precursor byproduct having sodium sulfate and the carbon material as raw materials includes: S1, performing a first purification treatment on the titanium dioxide byproduct to obtain a first purified solution; the first purification treatment can remove insoluble substances in the titanium dioxide byproduct, and the first purified solution includes ferrous sulfate heptahydrate and a plurality of soluble metal ions, wherein the soluble metal ions include Ni 2+ Mg 2+ and Mn 4+ At least two of the following; S2, performing a second purification treatment on the layered oxide precursor byproduct to obtain a second purified solution; the second purification treatment can remove ammonia nitrogen in the layered oxide precursor byproduct, and the second purified solution includes sodium sulfate and a plurality of soluble metal ions, wherein the soluble metal ions include Ni 2+ 、Co 2+ and Mn 4+ At least two of the following; S3, mixing and drying the first purified solution, the second purified solution and the carbon material to obtain a positive electrode material precursor; S4, granulating the positive electrode material precursor to obtain a precursor pressed material; S5, sintering the precursor pressed material and crushing it to obtain the sodium ion battery positive electrode material.
[0046] First, in step S1, the titanium dioxide by-product is a titanium dioxide by-product prepared by a sulfuric acid method. The impurities in the titanium dioxide by-product except ferrous sulfate heptahydrate mainly include insoluble substances and soluble metal ions, wherein the soluble metal ions are all in the form of sulfates and do not contain other anions that may affect the battery system. In the subsequent synthesis of sodium ferric sulfate, the soluble metal ions can exist in the crystal structure of sodium ferric sulfate in the form of doping, thereby improving the rate and cycle performance of the sodium ion battery positive electrode material. The first purification treatment in step S1 is mainly used to remove insoluble substances, including insoluble titanium dioxide and other insoluble impurities (for example, dust, etc.).
[0047] Specifically, the titanium dioxide by-product is subjected to a first purification treatment to obtain a first purified solution, that is, step S1 includes: S11, dissolving the titanium dioxide byproduct in deionized water, and dispersing iron powder in the deionized water to obtain a first initial solution; S12, mixing the sodium hydroxide solution and the first initial solution until the pH of the first initial solution reaches a first target pH, and filtering to obtain a filtrate; S13, mixing sulfuric acid, an antioxidant, and the filtrate until the pH of the filtrate reaches a second target pH, to obtain the first purified solution.
[0048] Compared with the traditional process of recovering ferrous sulfate heptahydrate from these by-products and using it as a sewage treatment agent or soil conditioner, which has low added value, or requiring high-purity purification before it can be used in the battery industry, which results in additional costs, the first purification treatment has lower purification requirements for the titanium dioxide by-product, which can further save the energy consumption and environmental protection costs required for the waste treatment of titanium dioxide by-products.
[0049] Among them, in step S11, the titanium dioxide by-product also has Fe 3+ , or Fe in titanium dioxide byproduct 2+ After dissolving in deionized water, it is easily oxidized to Fe 3+ , add iron powder to deionized water, the iron powder plays a reducing role and can be used to reduce the Fe 3+ Reduction to Fe 2+ , to increase Fe 2+ concentration, which is beneficial to improve the specific capacity of the prepared sodium ion battery positive electrode material; in some exemplary embodiments, the titanium dioxide byproduct is dissolved in deionized water at room temperature, and iron powder is added to the solution to reduce Fe in the solution. 3+, stirring for 0.5h~2h, improve the dissolution and dispersion uniformity of titanium dioxide by-products, and also help promote the iron powder to Fe 3+ The first initial solution is obtained by reduction, wherein the iron element in the first initial solution is mainly in the form of divalent iron ions Fe 2+ exists in the form of.
[0050] Specifically, in some exemplary embodiments, the mass percentage between the iron powder and ferrous sulfate heptahydrate is 0.1% to 1%; it can be understood that the mass percentage between the iron powder and ferrous sulfate heptahydrate can be any value between 0.1% and 1%; illustratively, the mass percentage between the iron powder and ferrous sulfate heptahydrate can be 0.1%, 0.2%, 0.5%, 0.7%, 0.8%, 1%, etc.; the mass percentage between the iron powder and the ferrous sulfate heptahydrate in the titanium dioxide byproduct is within this range, which can provide sufficient iron powder to remove Fe that may exist in the solution. 3+ Effective reduction is beneficial to maintain the Fe 2+ The stability of the cathode material will be improved, which will help improve the preparation yield of the cathode material for sodium ion batteries and improve the specific capacity and other properties of the cathode material for sodium ion batteries.
[0051] Specifically, in some exemplary embodiments, the concentration of ferrous sulfate heptahydrate in the first initial solution is 50 g / L to 150 g / L; it can be understood that the concentration of ferrous sulfate heptahydrate in the first initial solution can be any point value between 50 g / L and 150 g / L; illustratively, the concentration of ferrous sulfate heptahydrate in the first initial solution can be 50 g / L, 70 g / L, 80 g / L, 100 g / L, 120 g / L, 150 g / L, etc.; in this way, ferrous sulfate heptahydrate can be fully dissolved in the first initial solution, is not prone to precipitation, and can provide sufficient iron source in the subsequent S3-S5 steps to generate sodium ferric sulfate, thereby improving the preparation accuracy and preparation yield of the positive electrode material for sodium ion batteries.
[0052] Next, in step S12, the sodium hydroxide solution is used to adjust the pH of the first initial solution, and the pH of the sodium hydroxide solution is 10-13; it can be understood that the pH of the sodium hydroxide solution can be any point value between 10 and 13; illustratively, the pH of the sodium hydroxide solution can be 10, 10.5, 11, 11.7, 12, 13, etc.; in this way, the pH of the first initial solution can be effectively increased, so that some other undesirable cations in the first initial solution are precipitated and removed during the filtration process, which is beneficial to improve the accuracy of the metal ion doping type in the final sodium ion battery positive electrode material and improve the performance of the sodium ion battery positive electrode material; in addition, the sodium ions in the sodium hydroxide solution can also be used as part of the sodium source in the subsequent preparation process, and finally used to form the positive electrode material to improve the capacity of the sodium ion battery positive electrode material.
[0053] Specifically, titanium dioxide byproducts also include soluble Ti 2+ , which will have an adverse effect on the performance of the positive electrode material of the sodium ion battery; in the process of dissolving the titanium dioxide byproduct in deionized water, Ti 2+ Also dissolved in deionized water, thus existing in the first initial solution, while Ti 2+ The solubility under different pH conditions is different. In step S12, the sodium hydroxide solution can adjust the pH of the first initial solution to the first target pH. Under the first target pH, the Ti in the first initial solution 2+ A precipitation reaction occurs to form an insoluble titanium precipitate. Sodium hydroxide solution is added to the first initial solution and stirred for 0.2 h to 2 h to allow Ti 2+ Sufficient precipitation allows the titanium precipitate, insoluble matter and residual iron powder to be removed together during the filtration process. The impurity removal process is simple and efficient, and the impurity removal effect is good.
[0054] Specifically, the first target pH is 4.5 to 5; it can be understood that the first target pH can be any point value between 4.5 and 5; illustratively, the first target pH can be 4.5, 4.55, 4.6, 4.7, 4.8, 4.9, 5, etc.; within the first target pH range, Ti 2+ Effective precipitation occurs to increase Ti 2+ The removal efficiency of Ti 2+ Adverse effects on the performance of the positive electrode material of the sodium ion battery; and the first target pH is Fe 2+ The boundary pH of precipitation can effectively avoid Fe 2+ Precipitation occurs, which improves the solution stability of the first initial solution and the filtrate, and is beneficial to improving the final preparation yield and preparation reliability of the sodium ion battery positive electrode material.
[0055] Specifically, in step S12, the insoluble substances in the titanium dioxide by-product removed by filtration include titanium dioxide, and the mass proportion of titanium dioxide in the titanium dioxide by-product is less than the first mass proportion, and the first mass proportion is 0.7% to 1.3%; it can be understood that the first mass proportion can be any point value between 0.7% and 1.3%, which is not enumerated here; in this way, it is convenient to remove titanium dioxide by filtration, and it is not easy to affect the performance of the positive electrode material of the sodium ion battery; in some preferred embodiments, the first mass proportion is 1%, that is, the mass proportion of titanium dioxide in the titanium dioxide by-product is less than 1%; in addition, the insoluble substances in the titanium dioxide by-product also include insoluble impurities, such as dust, particles, etc., and the mass proportion of insoluble impurities in the titanium dioxide by-product is less than 1%, which can be effectively removed by filtration.
[0056] Next, in step S13, sulfuric acid is used to adjust the pH of the filtrate or the first purified solution, and sulfuric acid is added to the filtrate so that the pH of the filtrate reaches a second target pH, and the second target pH is 2 to 3.5; it can be understood that the second target pH can be any point value between 2 and 3.5; illustratively, the second target pH can be 2, 2.1, 2.5, 2.8, 3, 3.2, 3.5, etc.; within the second target pH range, Fe 2+ Precipitation occurs, which effectively maintains the stability of the first purified solution, improves the stability and reliability of the preparation method, and is beneficial to improving the preparation accuracy and preparation yield of the sodium ion battery positive electrode material.
[0057] Among them, the mass proportion of various soluble metal ions retained in the first purified solution in the titanium dioxide by-product is less than the second mass proportion, that is, Ni 2+ Mg 2+ and Mn 4+ The total mass of the titanium dioxide by-product has a mass proportion less than the second mass proportion, and the second mass proportion is 0.7% to 1.3%; it can be understood that the second mass proportion can be any point value between 0.7% and 1.3%, which is not enumerated here; in this way, the desired content of metal ions can be doped into the crystal structure of sodium iron sulfate in the subsequent preparation steps, greatly improving the specific capacity, rate performance and cycle performance of the positive electrode material of the sodium ion battery; in some preferred embodiments, the second mass proportion is 1%, that is, Ni 2+ Mg 2+ and Mn 4+ The total mass of titanium dioxide by-products accounts for less than 1%.
[0058] Specifically, in some exemplary embodiments, the antioxidant in step S13 includes at least one of ascorbic acid, oxalic acid and citric acid, and has excellent antioxidant properties; in the process of mixing sulfuric acid, the antioxidant and the filtrate, the antioxidant can effectively prevent the divalent iron ions (Fe 2+ ) is oxidized, which is beneficial to maintaining the stability of the filtrate and the first purified solution, and further beneficial to improving the rate performance and cycle performance of the prepared sodium ion battery positive electrode material.
[0059] Specifically, in some exemplary embodiments, the mass percentage between the antioxidant and ferrous sulfate heptahydrate is 0.1% to 3%; it can be understood that the mass percentage between the antioxidant and ferrous sulfate heptahydrate can be any point value between 0.1% and 3%; illustratively, the mass percentage between the antioxidant and ferrous sulfate heptahydrate can be 0.1%, 0.2%, 0.5%, 1.0%, 1.5%, 2%, 2.5%, 3%, etc.; in this way, Fe 2+It is oxidized, which improves the electrical properties of the sodium-ion battery positive electrode material, such as specific capacity and cycle stability.
[0060] Through the first purification treatment in step S1, the insoluble matter, the iron powder remaining during the treatment process and the Ti converted into titanium precipitate are 2+ was effectively removed, and the first purified solution obtained mainly included ferrous sulfate heptahydrate and Ni 2+ Mg 2+ and Mn 4+ The metal ion impurities can improve the performance of the final sodium ion battery positive electrode material in the form of doping; and the first purified solution also includes a small amount of Na introduced by the sodium hydroxide solution. + , which can be used as a part of the sodium source to generate sodium ferric sulfate, thereby increasing the capacity of the positive electrode material of the sodium ion battery; the first purified solution also includes an antioxidant to further maintain the stability of ferrous sulfate heptahydrate, which is beneficial to improving the reliability of the preparation method and the preparation yield of the positive electrode material of the sodium ion battery.
[0061] Specifically, the second purification treatment of the layered oxide precursor byproduct to obtain a second purified solution, that is, step S2, includes: S21, deammoniating the layered oxide precursor byproduct to obtain a second initial solution; S22, mixing sulfuric acid and the second initial solution until the pH of the second initial solution reaches a third target pH, to obtain the second purified solution.
[0062] Compared with the existing waste liquid treatment process including deammoniation recovery, precipitation, and MVR evaporation to obtain high-purity sodium sulfate powder (i.e., "sodium sulfate"), the second purification treatment has lower requirements for the purification of layered oxide precursor by-products, which is conducive to reducing the difficulty and cost of purification, further reducing the energy consumption and environmental problems caused by the recycling of by-products, and reducing the cost of waste treatment and recycling; and, compared with the process of preparing sodium iron sulfate positive electrode materials with high-purity raw materials, it can greatly reduce the production cost of the positive electrode material; that is, while improving the recycling rate of industrial waste and reducing the energy consumption and environmental protection cost of waste treatment, it can also use a relatively simple process to prepare positive electrode materials with relatively good rate performance and cycle performance using industrial waste as raw materials.
[0063] In step S2, the layered oxide precursor by-product mainly includes sodium sulfate, and in the process of preparing the layered oxide precursor by-product, the raw materials used are all sulfates, so that the anions in the layered oxide precursor by-product are all SO 4 2- , there are no other anions that affect the battery system, and a small amount of Ni 2+ 、Co 2+ and Mn4+ Metal ion impurities can also be used as doping elements to improve the performance of sodium ion battery positive electrode materials. The second purification treatment is used to remove ammonia nitrogen in the layered oxide precursor by-products and regulate the pH of the second purified solution.
[0064] Specifically, the concentration of sodium sulfate in the layered oxide precursor by-product is 50 g / L to 200 g / L; it can be understood that the concentration of sodium sulfate in the layered oxide precursor by-product can be any point value between 50 g / L and 200 g / L; illustratively, the concentration of sodium sulfate in the layered oxide precursor by-product can be 50 g / L, 70 g / L, 100 g / L, 120 g / L, 150 g / L, 180 g / L, 200 g / L, etc.; in this way, a rich sodium source can be provided to generate sodium iron sulfate, thereby increasing the yield of positive electrode materials for sodium ion batteries.
[0065] Specifically, in step S21, the pH of the layered oxide precursor by-product is greater than 12; it is understandable that the pH of the layered oxide precursor by-product can be any value greater than 12, which is not enumerated here; the ammonia nitrogen content in the layered oxide precursor by-product is 5g / L to 10g / L; it is understandable that the ammonia nitrogen content in the layered oxide precursor by-product can be any value in the range of 5g / L to 10g / L, which is not enumerated here; the deamination treatment is used to remove ammonia nitrogen in the layered oxide precursor by-product, which can be carried out by a distillation tower Deamination treatment is performed to obtain a second initial solution that does not contain ammonia. In an alkaline environment, it is beneficial to remove ammonia by distillation in step S21, and the discharge of ammonia during the removal process promotes the reversible reaction between ammonium ions and ammonia in the direction of generating ammonia, thereby further removing ammonia nitrogen in the by-products of the layered oxide precursor, and improving the deamination efficiency and ammonia nitrogen removal rate. In addition, the discharged ammonia can be converted into ammonia water after absorption, thereby realizing the recovery of by-product ammonia, which can be further used for pH control in other precursor preparation processes, with a high recovery rate and greatly reduced pollution.
[0066] Specifically, the content of the various soluble metal ions retained in the second purified solution in the layered oxide precursor byproduct is 75 mg / L to 130 mg / L, i.e., Ni 2+ 、Co 2+ and Mn 4+ The content of Ni in the layered oxide precursor byproduct is 75mg / L to 130mg / L; it can be understood that Ni 2+ 、Co 2+ and Mn 4+The content of the layered oxide precursor byproduct can be any point value in the range of 75 mg / L to 130 mg / L, which is not enumerated here; in this way, the desired content of metal ions can be doped into the crystal structure of sodium iron sulfate in the subsequent preparation steps, greatly improving the specific capacity, rate performance and cycle performance of the positive electrode material of the sodium ion battery; in some specific embodiments, Ni 2+ 、Co 2+ and Mn 4+ The content in the layered oxide precursor by-product may be about 100 mg / L.
[0067] Specifically, in step S22, sulfuric acid is added to the second initial solution to adjust the pH of the second initial solution or the second purified solution to a third target pH, and the third target pH is 6.7 to 7.0; it can be understood that the third target pH can be any point value between 6.7 and 7.0; illustratively, the third target pH can be 6.7, 6.75, 6.8, 6.9, 7.0, etc.; within the third target pH range, the cations in the second initial solution can be effectively prevented from precipitating, the stability of the second purified solution can be effectively maintained, the stability and reliability of the preparation method of the sodium ion battery positive electrode material can be improved, and it is beneficial to improve the preparation accuracy and preparation yield of the sodium ion battery positive electrode material.
[0068] Next, after obtaining the first purified solution in step S1 and the second purified solution in step S2, a positive electrode material for a sodium ion battery is prepared based on the first purified solution, the second purified solution and the carbon material, and a positive electrode material precursor is prepared in step S3. Then, in step S4, the positive electrode material precursor is granulated to obtain a precursor pressed material. The precursor pressed material is a block structure with a certain shape and not loose, which is convenient for subsequent sintering and improves the sintering effect. Finally, in step S5, the precursor pressed material is granulated in a preset atmosphere environment. The sodium ion battery cathode material is sintered and crushed to obtain the sodium ion battery cathode material. The preparation method of the sodium ion battery cathode material has low overall cost and low preparation difficulty, and has low purity requirements for sodium ferrous sulfate heptahydrate and sodium sulfate raw materials. The preparation of battery-grade sodium ion battery cathode material from industrial waste can be directly realized, which greatly saves the energy consumption and environmental protection costs caused by the waste coarse particles of titanium dioxide by-products and layered oxide precursor by-products, and also greatly simplifies the production process of the sodium ion battery cathode material, thereby reducing the production cost of the sodium ion battery cathode material.
[0069] Specifically, in some exemplary embodiments, the first purified solution, the second purified solution and the carbon material are mixed and dried to obtain a positive electrode material precursor, that is, step S3 includes: According to a preset x / y value, the first purified solution, the second purified solution, and the carbon material are mixed to obtain a precursor solution; The precursor solution is dried to obtain the positive electrode material precursor.
[0070] Specifically, in some other exemplary embodiments, the first purified solution, the second purified solution and the carbon material are mixed and dried to obtain a positive electrode material precursor, that is, step S3 includes: According to a preset x / y value, the first purified solution and the second purified solution are mixed to obtain a precursor solution; Drying the precursor solution to obtain a precursor solid; The carbon material and the precursor solid are mixed and ball-milled to obtain the positive electrode material precursor.
[0071] Specifically, in other exemplary embodiments, the first purified solution, the second purified solution and the carbon material are mixed and dried to obtain a positive electrode material precursor, that is, step S3 includes: According to a preset x / y value, the first purified solution, the second purified solution, and the carbon material are mixed to obtain a precursor solution; Drying the precursor solution to obtain a precursor solid; The carbon material and the precursor solid are mixed and ball-milled to obtain the positive electrode material precursor.
[0072] That is, in step S3, the carbon material can be added to the precursor solution during the process of mixing the first purified solution and the second purified solution; or the carbon material can be dry-mixed with the precursor solid after the first purified solution and the second purified solution are mixed and dried; or the carbon material can be added in both steps. The preparation method of the positive electrode material for sodium ion batteries is flexible and has a wide range of applications.
[0073] In some exemplary embodiments, the obtained precursor solution is a uniform non-stratified solution. After the first purified solution and the second purified solution (or also including carbon material) are mixed and stirred, sand grinding can be performed to improve the uniformity of the precursor solution.
[0074] Specifically, in some exemplary embodiments, in the first purified solution and the second purified solution used to prepare the positive electrode material precursor in step S3, the preset x / y value between the sodium element and the iron element is 1 to 2. During the preparation process, the first purified solution and the second purified solution can be subjected to ICP testing to obtain the iron content and the sodium content. Based on the measured iron content and the sodium content, the mass of the first purified solution and the second purified solution, as well as the mass of the carbon material to be added, are determined to prepare the positive electrode material precursor; it can be understood that the preset x / y value between the sodium element and the iron element is 1 to 2. Assume that the x / y value can be any point value between 1 and 2; illustratively, the preset x / y value between the sodium element and the iron element can be 1, 1.1, 1.2, 1.5, 1.7, 1.8, 1.9, 2, etc.; in this way, the specific capacity of the prepared sodium ion battery positive electrode material can be improved, and the rate performance and cycle performance of the sodium ion battery positive electrode material can be improved; further, in some exemplary embodiments, the preset x / y value between the sodium element and the iron element is 1.2 to 1.8; in some preferred embodiments, the preset x / y value between the sodium element and the iron element is 1.3 to 1.7.
[0075] Specifically, in some exemplary embodiments, in the process of mixing the first purified solution, the second purified solution, and the carbon material according to a preset x / y value to obtain a precursor solution, the mass of the carbon material is 0.1% to 5% of the total mass of ferrous sulfate heptahydrate and sodium sulfate; it can be understood that the mass of the carbon material can be any point value between 0.1% and 5% of the total mass of ferrous sulfate heptahydrate and sodium sulfate; illustratively, the mass of the carbon material can be 0.1%, 0.5%, 1%, 3%, 5%, etc. of the total mass of ferrous sulfate heptahydrate and sodium sulfate; in this way, the conductivity of the prepared sodium ion battery positive electrode material can be effectively improved, and the rate performance and cycle performance of the sodium ion battery positive electrode material can be improved.
[0076] Specifically, in the process of drying the precursor solution, the drying treatment includes at least one of freeze drying, evaporative drying, spray drying and steam mechanical recompression (MVR) to effectively remove moisture from the precursor solution; in some exemplary embodiments, the precursor solution is spray dried, the inlet air temperature is 180°C to 220°C, and the outlet air temperature is 90°C to 120°C; it can be understood that the inlet air temperature can be any point value between 180°C and 220°C, and the outlet air temperature can be any point value between 90°C and 120°C, which are not enumerated here, and the moisture in the precursor solution can be effectively removed.
[0077] Specifically, in some exemplary embodiments, in the process of mixing the carbon material and the precursor solid matter and ball milling to obtain the positive electrode material precursor, the mass of the carbon material is 0.1% to 5% of the mass of the precursor solid matter; it can be understood that the mass of the carbon material can be any point value between 0.1% and 5% of the mass of the precursor solid matter, which is not enumerated here; in this way, the conductivity of the prepared sodium ion battery positive electrode material can be effectively improved, and the rate performance and cycle performance of the sodium ion battery positive electrode material can be improved.
[0078] Specifically, the ball milling treatment may include at least one of planetary ball milling, vibration ball milling and stirring ball milling. Correspondingly, the ball milling can be performed by at least one of the ball milling equipments including a planetary ball mill, a vibration ball mill and a stirring ball mill, which can effectively improve the mixing uniformity of the precursor solid and the carbon material, reduce the particle size of the positive electrode material precursor, and is beneficial to improve the sintering effect of the subsequent sintering step, thereby improving the preparation yield of the positive electrode material for the sodium ion battery.
[0079] Specifically, in some exemplary embodiments, during the ball milling process, the ball-to-material ratio of the total mass of the precursor solid and the carbon material to the ball milling medium is 10:1 to 50:1, and the ball milling time is 0.2h to 5h; it can be understood that the ball-to-material ratio of the total mass of the precursor solid and the carbon material to the ball milling medium can be any point value between 10:1 and 50:1, and the ball milling time can be any point value between 0.2h and 5h, which are no longer enumerated here; in this way, the dispersibility and uniformity of the carbon material and the precursor solid can be effectively improved, and the particle size of the positive electrode material precursor can be reduced, which is beneficial to improving the subsequent doping effectiveness and uniformity of multiple metal ions in the sodium iron sulfate crystal structure, and is also beneficial to improving the sintering effect in the subsequent sintering process, improving the molding accuracy of the sodium ion battery positive electrode material, and improving the preparation stability and preparation reliability, which is beneficial to improving the performance of the prepared sodium ion battery positive electrode material.
[0080] Next, in the granulation process of step S4, granulation can be performed by a granulation device such as a tablet press, a roller granulator, and a press, and the target density of the precursor pressed material is 2.0 g / cm 3 ~3.0g / cm 3 It can be understood that the target density of the precursor pressed material can be 2.0g / cm 3 ~3.0g / cm 3 For example, the target density of the precursor pressed material can be 2.0 g / cm 3 , 2.1g / cm 3 , 2.2g / cm 3 , 2.5g / cm 3 , 2.7g / cm 3 , 3.0g / cm3 Etc.; in this way, the contact tightness between the materials in the precursor pressing material can be effectively improved, which is beneficial to improving the sintering effect, improving the morphology accuracy and performance of the sodium ion battery positive electrode material, and when a roller kiln is used for sintering, the production capacity of the kiln can also be improved, further improving the economy of the preparation method of the sodium ion battery positive electrode material.
[0081] Specifically, in step S5, during the sintering process of the precursor pressed material, the preset atmosphere environment includes nitrogen, argon, etc., so as to effectively play a protective role and improve the sintering effect. The sintering temperature is 350°C to 400°C, and the sintering time is 4h to 15h; it can be understood that the sintering temperature can be any point value between 350°C and 400°C, and the sintering time can be any point value between 4h and 15h; illustratively, the sintering temperature can be 350°C, 360°C, 370°C, 375°C, 380°C, 390°C, 400°C, etc., and the sintering time can be 4h, 6h h, 8h, 9h, 10h, 11h, 13h, 15h, etc.; the sintering process undergoes a pure solid-phase reaction, which can enable the iron element and the sodium element in the precursor pressing material to fully react to generate sodium ferric sulfate, and can also promote the doping of various metal ion impurities into the crystal structure of sodium ferric sulfate. The sintering effect is good, which is beneficial to improving the specific capacity and other properties of the sodium ion battery positive electrode material. In addition, crushing after sintering can also improve the convenience of using the sodium ion battery positive electrode material in sodium ion batteries; in some preferred embodiments, the sintering temperature is 350°C to 370°C, and the sintering time is 8h to 12h.
[0082] On the other hand, an embodiment of the present application further provides a sodium ion battery, comprising the sodium ion battery positive electrode material as described above, or comprising the sodium ion battery positive electrode material prepared by the preparation method of the sodium ion battery positive electrode material as described above, so that the sodium ion battery has good rate performance and cycle performance, and the preparation process is simple and the preparation difficulty is low, and the preparation process flow from industrial by-products to sodium ion batteries is realized, which greatly reduces the energy consumption and environmental protection costs caused by industrial waste treatment, and uses industrial by-products as raw materials to reduce the preparation cost of sodium ion batteries.
[0083] The following describes the embodiments of the present application in combination with the above technical solutions.
[0084] Example 1 like Figure 1 As shown, the positive electrode material of the sodium ion battery of this embodiment is prepared by the following steps: 1. Dissolve the titanium dioxide byproduct in deionized water, and disperse the iron powder in deionized water, and stir for 0.5 h to obtain a first initial solution; wherein the mass of the iron powder is 0.5% of the mass of ferrous sulfate heptahydrate, and the concentration of ferrous sulfate heptahydrate in the first initial solution is 120 g / L; 2. Mixing a sodium hydroxide solution with a pH of 12 and the first initial solution until the pH of the first initial solution reaches 4.5, stirring for 1 hour and then filtering to obtain a filtrate; 3. Sulfuric acid, ascorbic acid and the filtrate are mixed until the pH of the filtrate is 3.0 to obtain a first purified solution; the ICP result of the first purified solution shows that the iron content is 23.7% and the sodium content is 1.3%; 4. Deaminate the layered oxide precursor byproduct to obtain a second initial solution, and mix sulfuric acid with the second initial solution until the pH of the second initial solution is 7.0 to obtain a second purified solution; the ICP result of the second purified solution shows that the sodium content is 3.12%; 5. According to the above ICP results, the first purified solution, the second purified solution, and the carbon nanotubes were mixed according to the preset x / y value = 1.5, stirred evenly, and then sand-milled to obtain a precursor solution; wherein the mass of the carbon nanotubes is 3% of the total mass of ferrous sulfate heptahydrate and sodium sulfate in the solution; 6. The precursor solution is spray dried with an inlet air temperature of 200°C and an outlet air temperature of 110°C to obtain a gray-black precursor solid; 7. The precursor solid and carbon nanotubes were mixed in a mass ratio of 98:2, and ball milled in a vibration ball mill at a ball-to-material ratio of 10:1 for 2 hours to obtain a positive electrode material precursor; 8. Granulate the cathode material precursor to obtain a compact precursor pressed material; 9. Place the precursor pressed material in a roller kiln, sinter it in a nitrogen atmosphere at a sintering temperature of 360°C for 10 hours, and crush it to obtain a sodium ion battery positive electrode material.
[0085] Example 2 The positive electrode material of the sodium ion battery of this embodiment is prepared by the following steps: 1. Dissolve the titanium dioxide byproduct in deionized water, and disperse the iron powder in deionized water, and stir for 0.5h to obtain a first initial solution; wherein the mass of the iron powder is 0.7% of the mass of ferrous sulfate heptahydrate, and the concentration of ferrous sulfate heptahydrate in the first initial solution is 150g / L; 2. Mix the sodium hydroxide solution with a pH of 12 and the first initial solution until the pH of the first initial solution reaches 4.7, stir for 1 hour and then filter to obtain a filtrate; 3. Sulfuric acid, ascorbic acid and the filtrate are mixed until the pH of the filtrate is 3.0 to obtain a first purified solution; the ICP result of the first purified solution shows that the iron content is 28.7% and the sodium content is 1.6%; 4. Deaminate the layered oxide precursor byproduct to obtain a second initial solution, and mix sulfuric acid with the second initial solution until the pH of the second initial solution is 6.8 to obtain a second purified solution; the ICP result of the second purified solution shows that the sodium content is 3.14%; 5. According to the above ICP results, according to the preset x / y value = 1.6, the first purified solution, the second purified solution, and the carbon nanotubes are mixed, stirred evenly, and then sand-milled to obtain a precursor solution; wherein the mass of the carbon nanotubes is 2% of the total mass of ferrous sulfate heptahydrate and sodium sulfate in the solution; 6. The precursor solution is spray dried with an inlet air temperature of 200°C and an outlet air temperature of 110°C to obtain a gray-black precursor solid; 7. The precursor solid and carbon nanotubes were mixed in a mass ratio of 98:2, and ball milled in a vibration ball mill at a ball-to-material ratio of 10:1 for 2 hours to obtain a positive electrode material precursor; 8. Granulate the cathode material precursor to obtain a compact precursor pressed material; 9. Place the precursor pressed material in a roller kiln, sinter it in a nitrogen atmosphere at a sintering temperature of 360°C for 10 hours, and crush it to obtain a sodium ion battery positive electrode material.
[0086] Example 3 The positive electrode material of the sodium ion battery of this embodiment is prepared by the following steps: 1. Dissolve the titanium dioxide byproduct in deionized water, and disperse the iron powder in deionized water, and stir for 0.5h to obtain a first initial solution; wherein the mass of the iron powder is 0.3% of the mass of ferrous sulfate heptahydrate, and the concentration of ferrous sulfate heptahydrate in the first initial solution is 100g / L; 2. Mixing a sodium hydroxide solution with a pH of 12 and the first initial solution until the pH of the first initial solution reaches 4.5, stirring for 1 hour and then filtering to obtain a filtrate; 3. Sulfuric acid, ascorbic acid and the filtrate are mixed until the pH of the filtrate is 2.5 to obtain a first purified solution; the ICP result of the first purified solution shows that the iron content is 18.7% and the sodium content is 0.9%; 4. Deaminate the layered oxide precursor byproduct to obtain a second initial solution, and mix sulfuric acid with the second initial solution until the pH of the second initial solution is 7.0 to obtain a second purified solution; the ICP result of the second purified solution shows that the sodium content is 3.10%; 5. According to the above ICP results, according to the preset x / y value = 1.35, the first purified solution, the second purified solution, and the carbon nanotubes are mixed, stirred evenly, and then sand-milled to obtain a precursor solution; wherein the mass of the carbon nanotubes is 2% of the total mass of ferrous sulfate heptahydrate and sodium sulfate in the solution; 6. The precursor solution is spray dried with an inlet air temperature of 200°C and an outlet air temperature of 110°C to obtain a gray-black precursor solid; 7. The precursor solid and carbon nanotubes were mixed in a mass ratio of 98:2, and ball milled in a vibration ball mill at a ball-to-material ratio of 10:1 for 2 hours to obtain a positive electrode material precursor; 8. Granulate the cathode material precursor to obtain a compact precursor pressed material; 9. Place the precursor pressed material in a roller kiln, sinter it in a nitrogen atmosphere at a sintering temperature of 360°C for 10 hours, and crush it to obtain a sodium ion battery positive electrode material.
[0087] Example 4 The positive electrode material of the sodium ion battery of this embodiment is prepared by the following steps: 1. Dissolve the titanium dioxide byproduct in deionized water, and disperse the iron powder in deionized water, and stir for 0.5 h to obtain a first initial solution; wherein the mass of the iron powder is 0.5% of the mass of ferrous sulfate heptahydrate, and the concentration of ferrous sulfate heptahydrate in the first initial solution is 120 g / L; 2. Mixing a sodium hydroxide solution with a pH of 12 and the first initial solution until the pH of the first initial solution reaches 4.5, stirring for 1 hour and then filtering to obtain a filtrate; 3. Sulfuric acid, ascorbic acid and the filtrate are mixed until the pH of the filtrate is 3.0 to obtain a first purified solution; the ICP result of the first purified solution shows that the iron content is 23.9% and the sodium content is 1.1%; 4. Deaminate the layered oxide precursor byproduct to obtain a second initial solution, and mix sulfuric acid with the second initial solution until the pH of the second initial solution is 7.0 to obtain a second purified solution; the ICP result of the second purified solution shows that the sodium content is 3.16%; 5. According to the above ICP results, according to the preset x / y value = 1.5, the first purified solution and the second purified solution are mixed and stirred evenly to obtain a precursor solution; 6. The precursor solution is spray dried with an inlet air temperature of 200°C and an outlet air temperature of 110°C to obtain a gray-black precursor solid; 7. The precursor solid and carbon nanotubes were mixed in a mass ratio of 97:3, and ball milled in a vibration ball mill at a ball-to-material ratio of 10:1 for 2 hours to obtain a positive electrode material precursor; 8. Granulate the cathode material precursor to obtain a compact precursor pressed material; 9. Place the precursor pressed material in a roller kiln, sinter it in a nitrogen atmosphere at a sintering temperature of 360°C for 10 hours, and crush it to obtain a sodium ion battery positive electrode material.
[0088] Example 5 The positive electrode material of the sodium ion battery of this embodiment is prepared by the following steps: 1. Dissolve the titanium dioxide byproduct in deionized water, and disperse the iron powder in deionized water, and stir for 0.5h to obtain a first initial solution; wherein the mass of the iron powder is 0.4% of the mass of ferrous sulfate heptahydrate, and the concentration of ferrous sulfate heptahydrate in the first initial solution is 120g / L; 2. Mixing a sodium hydroxide solution with a pH of 12 and the first initial solution until the pH of the first initial solution reaches 4.5, stirring for 1 hour and then filtering to obtain a filtrate; 3. Sulfuric acid, ascorbic acid and the filtrate are mixed until the pH of the filtrate is 3.0 to obtain a first purified solution; the ICP result of the first purified solution shows that the iron content is 24.0% and the sodium content is 1.0%; 4. Deaminate the layered oxide precursor byproduct to obtain a second initial solution, and mix sulfuric acid with the second initial solution until the pH of the second initial solution is 7.0 to obtain a second purified solution; the ICP result of the second purified solution shows that the sodium content is 3.17%; 5. According to the above ICP results, the first purified solution, the second purified solution, and the carbon nanotubes were mixed according to the preset x / y value = 1.5, stirred evenly, and then sand-milled to obtain a precursor solution; wherein the mass of the carbon nanotubes is 3% of the total mass of ferrous sulfate heptahydrate and sodium sulfate in the solution; 6. The precursor solution is spray dried with an inlet air temperature of 200°C and an outlet air temperature of 110°C to obtain a gray-black cathode material precursor; 7. Granulate the cathode material precursor to obtain a compact precursor pressed material; 8. The precursor pressed material is placed in a roller kiln, sintered in a nitrogen atmosphere at a sintering temperature of 360°C for 10 hours, and crushed to obtain a sodium ion battery positive electrode material.
[0089] Example 6 The difference between this embodiment and the first embodiment is that, in step 5, the preset x / y value is 1.8; the rest is the same as the first embodiment.
[0090] Example 7 The difference between this embodiment and the first embodiment is that, in step 5, the preset x / y value is 1.2; the rest is the same as the first embodiment.
[0091] Comparative Example 1 The difference between this comparative example and Example 1 is that, before step 5, a high-purity raw material is used for preparation, and the positive electrode material of the sodium ion battery in this comparative example is prepared by the following steps: 1. Disperse high-purity ferrous sulfate heptahydrate (ferrous sulfate heptahydrate content> 99.8%, impurity element content less than 100ppm) into deionized water, the concentration of ferrous sulfate heptahydrate is 120g / L, and add ascorbic acid with a mass% of ferrous sulfate heptahydrate. After stirring for 0.5h, a clear green first solution is obtained. The ICP result of the first solution shows that the iron content is 24.2%; 2. Disperse high-purity sodium sulfate (sodium sulfate content> 99.9%, impurity element content less than 100 ppm) into deionized water and stir for 1 hour to obtain a second solution; the sodium sulfate concentration in the second solution is 100 g / L, and the ICP result of the second solution shows that the sodium content is 3.24%; 3. According to the above ICP results, according to the preset x / y value = 1.5, the first solution, the second solution, and the carbon nanotubes are mixed, stirred evenly, and then sand-milled to obtain a precursor solution; wherein the mass of the carbon nanotubes is 3% of the total mass of ferrous sulfate heptahydrate and sodium sulfate in the solution; 6. The precursor solution is spray dried with an inlet air temperature of 200°C and an outlet air temperature of 110°C to obtain a gray-black precursor solid; 7. The precursor solid and carbon nanotubes were mixed in a mass ratio of 98:2, and ball milled in a vibration ball mill at a ball-to-material ratio of 10:1 for 2 hours to obtain a positive electrode material precursor; 8. Granulate the cathode material precursor to obtain a compact precursor pressed material; 9. Place the precursor pressed material in a roller kiln, sinter it in a nitrogen atmosphere at a sintering temperature of 360°C for 10 hours, and crush it to obtain a sodium ion battery positive electrode material.
[0092] Comparative Example 2 The difference between this comparative example and Example 1 is that no iron powder is added in step 1, and no sodium hydroxide solution is added in step 2; the rest is the same as Example 1.
[0093] Comparative Example 3 The difference between this comparative example and Example 1 is that, in step 5, the preset x / y value is 2.2; the rest is the same as Example 1.
[0094] Comparative Example 4 The difference between this embodiment and the first embodiment is that, in step 5, the preset x / y value is 0.9; the rest is the same as the first embodiment.
[0095] Table 1 Test results of discharge specific capacity of positive electrode materials for sodium ion batteries in Examples and Comparative Examples
[0096] Table 2 Test results of impurity element content of positive electrode materials for sodium ion batteries in some embodiments and some comparative examples
[0097] As shown in Table 1, compared with the sodium ion battery positive electrode material prepared using high-purity raw materials in Comparative Example 1, the sodium ion battery positive electrode materials prepared in Examples 1-7 of the present application all have good discharge specific capacity; further, the value of x / y in Examples 1-5 is within the range of 1.3 to 1.7, and the discharge specific capacity is greater than or equal to 92.8 mAh / g, especially in Examples 1-3, the discharge specific capacity reaches 95.3 mAh / g, 94.8 mAh / g and 95.9 mAh / g, respectively, which is very close to the specific capacity of 95.1 mAh / g in Comparative Example 1, that is, the sodium ion battery positive electrode material prepared by the preparation method of the sodium ion battery positive electrode material provided by the present application, its discharge specific capacity can be comparable to the discharge specific capacity of the positive electrode material prepared based on high-purity raw materials.
[0098] In the sodium ion battery positive electrode material without the first purification treatment in Comparative Example 2, as shown in Table 2, during the preparation process, more titanium ions remain, resulting in a significant decrease in the discharge specific capacity of the prepared sodium ion battery positive electrode material, while in Example 1, less titanium ions remain, and the effect on the performance of the sodium ion battery positive electrode material is almost negligible, while other metal ions (Ni 2+ Mg 2+ 、Co 2+ and Mn 4+ ) makes the sodium ion battery positive electrode material have good discharge specific capacity, rate performance and cycle performance; and the value of x / y in Comparative Examples 3-4 exceeds the range of 1 to 2, resulting in a significant decrease in the discharge specific capacity of the sodium ion battery positive electrode material in Comparative Examples 3-4, while in the embodiments of the present application, the values of x / y are all within the range of 1 to 2, so that the discharge specific capacity of the sodium ion battery positive electrode material is greater than 90 mAh / g.
[0099] In addition, if Figure 2As shown, according to the rate performance comparison data of Example 1 and Comparative Example 1, it can be seen that after metal ion doping, although the capacity of the sodium ion battery positive electrode material in Example 1 has decreased to a certain extent, the capacity retention rate at high rate is effectively improved, so that the sodium ion battery positive electrode material can be suitable for high rate application scenarios, expanding the scope of application of the sodium ion battery positive electrode material.
[0100] It can be seen that compared with the traditional process based on high-purity raw material preparation, the sodium ion battery positive electrode material and preparation method of the present application can realize the preparation process of sodium ion battery positive electrode material from industrial waste such as titanium dioxide by-products and layered oxide precursor by-products to batteries. On the one hand, it saves the energy consumption and environmental protection costs brought about by-product recovery and waste treatment. On the other hand, a sodium ion battery positive electrode material with better performance can be further obtained by simple purification treatment. The purification requirements are relatively low, which greatly simplifies the production process of sodium ion battery positive electrode materials. The large amount of by-products and easy availability also removes the restrictions on production capacity, further reducing the production cost of sodium ion battery positive electrode materials. At the same time, the risk of a significant decrease in the performance of sodium ion battery positive electrode materials is avoided, so that the prepared sodium ion battery positive electrode material has a specific capacity, rate performance and cycle performance similar to those of high-purity positive electrode materials.
[0101] It should be noted that the various embodiments in this specification are described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the various embodiments can be referenced to each other.
[0102] What is described above are only some embodiments of the present application and are not intended to limit the present application. Those skilled in the art should understand that the present application may undergo various changes and improvements, and any modifications, equivalent substitutions and improvements made in accordance with the present application shall fall within the scope of protection required by the present application.
Claims
1. A sodium ion battery positive electrode material, characterized in that: The positive electrode material of the sodium ion battery includes sodium iron sulfate, carbon material and multiple metal ions, wherein the carbon material is dispersed among the sodium iron sulfate, and the metal ions are doped in the crystal structure of the sodium iron sulfate; The sodium ion battery positive electrode material is prepared using an iron source, a layered oxide precursor byproduct having sodium sulfate, and a carbon material as raw materials; the layered oxide precursor byproduct includes metal ions, and the metal ions include Ni 2+ 、Co 2+ and Mn 4+ At least two of the .
2. The sodium ion battery positive electrode material according to claim 1, characterized in that The iron source is a titanium dioxide byproduct having ferrous sulfate heptahydrate, and the titanium dioxide byproduct and / or the layered oxide precursor byproduct include metal ions, and the metal ions include Ni 2+ Mg 2+ 、Co 2+ and Mn 4+ ; The chemical formula of the sodium ion battery positive electrode material is Na x Fe y Ni a Co b Mn c Mg d (SO4) z @C, where 1≤x / y≤2, (a+b+c+d) / y≤0.
1.
3. The sodium ion battery positive electrode material according to claim 2, characterized in that The sodium ion battery positive electrode material is obtained by performing a first purification treatment on a titanium dioxide byproduct to obtain a first purified solution, performing a second purification treatment on a layered oxide precursor byproduct to obtain a second purified solution, mixing the first purified solution, the second purified solution and a carbon material, drying them, and granulating and sintering them; The first purification treatment can remove insoluble substances in the titanium dioxide byproduct, and the first purification solution includes ferrous sulfate heptahydrate and a plurality of soluble metal ions, wherein the soluble metal ions include Ni 2+ Mg 2+ and Mn 4+ At least two of the following; The second purification treatment can remove ammonia nitrogen in the layered oxide precursor byproduct; the second purification solution includes sodium sulfate and a plurality of soluble metal ions, wherein the soluble metal ions include Ni 2+ 、Co 2+ and Mn 4+ At least two of the .
4. The sodium ion battery positive electrode material according to claim 3, characterized in that The first purified solution and the second purified solution are mixed according to a preset x / y value between the sodium element and the iron element by measuring the iron content and the sodium content in the first purified solution, measuring the sodium content in the second purified solution; wherein 1.2≤x / y≤1.
8.
5. A method for preparing a positive electrode material for a sodium ion battery, characterized in that: The sodium ion battery positive electrode material is prepared by using an iron source, a layered oxide precursor byproduct having sodium sulfate and a carbon material as raw materials; the layered oxide precursor byproduct includes metal ions, and the metal ions include Ni 2+ 、Co 2+ and Mn 4+ At least two of the following; The sodium ion battery positive electrode material comprises sodium ferric sulfate, a carbon material and a plurality of metal ions, wherein the carbon material is dispersed among the sodium ferric sulfate, and the metal ions are doped in the crystal structure of the sodium ferric sulfate.
6. The method for preparing a positive electrode material for a sodium ion battery according to claim 5, characterized in that: The iron source is a titanium dioxide byproduct having ferrous sulfate heptahydrate, and the titanium dioxide byproduct includes metal ions, and the metal ions include Ni 2 + Mg 2+ and Mn 4+ At least two of the above; the sodium ion battery positive electrode material prepared by using an iron source, a layered oxide precursor byproduct having sodium sulfate and a carbon material as raw materials comprises: The titanium dioxide byproduct is subjected to a first purification treatment to obtain a first purified solution; the first purification treatment can remove insoluble substances in the titanium dioxide byproduct, and the first purified solution includes ferrous sulfate heptahydrate and a plurality of soluble metal ions, wherein the soluble metal ions include Ni 2+ Mg 2+ and Mn 4+ At least two of the following; The layered oxide precursor byproduct is subjected to a second purification treatment to obtain a second purified solution; the second purification treatment can remove ammonia nitrogen in the layered oxide precursor byproduct, and the second purified solution includes sodium sulfate and a plurality of soluble metal ions, wherein the soluble metal ions include Ni 2+ 、Co 2+ and Mn 4+ At least two of the following; Mixing and drying the first purified solution, the second purified solution and the carbon material to obtain a positive electrode material precursor; Granulating the positive electrode material precursor to obtain a precursor pressed material; The precursor pressed material is sintered and crushed to obtain the sodium ion battery positive electrode material.
7. The method for preparing a positive electrode material for a sodium ion battery according to claim 6, characterized in that: The first purification process of the titanium dioxide byproduct to obtain a first purified solution comprises: Dissolving the titanium dioxide byproduct in deionized water and dispersing iron powder in the deionized water to obtain a first initial solution; The sodium hydroxide solution and the first initial solution are mixed until the pH of the first initial solution reaches a first target pH, and filtered to obtain a filtrate; the first target pH is 4.5-5; the titanium dioxide byproduct also includes Ti 2+ , in the case of the first target pH, the Ti in the first initial solution 2+ A precipitation reaction occurs to form an insoluble titanium precipitate; Sulfuric acid, an antioxidant and the filtrate are mixed until the pH of the filtrate reaches a second target pH to obtain the first purified solution; the second target pH is 2 to 3.
5.
8. The method for preparing a positive electrode material for a sodium ion battery according to claim 7, characterized in that: The titanium dioxide byproduct is subjected to a first purification treatment to obtain a first purified solution that satisfies at least one of the following characteristics: The insoluble matter of the titanium dioxide by-product includes titanium dioxide, and the mass proportion of the titanium dioxide in the titanium dioxide by-product is less than the first mass proportion, and the first mass proportion is 0.7% to 1.3%; The mass proportion of the multiple soluble metal ions of the first purified solution in the titanium dioxide by-product is less than the second mass proportion, and the second mass proportion is 0.7% to 1.3%; The concentration of ferrous sulfate heptahydrate in the first initial solution is 50 g / L to 150 g / L; The mass percentage between the iron powder and the ferrous sulfate heptahydrate is 0.1% to 1%; The pH of the sodium hydroxide solution is 10 to 13; The antioxidant comprises at least one of ascorbic acid, oxalic acid and citric acid; The mass percentage between the antioxidant and the ferrous sulfate heptahydrate is 0.1% to 3%.
9. The method for preparing a positive electrode material for a sodium ion battery according to claim 6, characterized in that: The step of performing a second purification treatment on the layered oxide precursor byproduct to obtain a second purified solution comprises: Deaminate the layered oxide precursor byproduct to obtain a second initial solution; Sulfuric acid and the second initial solution are mixed until the pH of the second initial solution reaches a third target pH, thereby obtaining the second purified solution; the third target pH is 6.7 to 7.
0.
10. The method for preparing a positive electrode material for a sodium ion battery according to claim 9, characterized in that: The second purification treatment is performed on the layered oxide precursor byproduct to obtain a second purified solution that satisfies at least one of the following characteristics: The pH of the layered oxide precursor byproduct is greater than 12; The concentration of sodium sulfate in the layered oxide precursor byproduct is 50 g / L to 200 g / L; The ammonia nitrogen content in the layered oxide precursor byproduct is 5 g / L to 10 g / L; The content of the plurality of soluble metal ions of the second purified solution in the layered oxide precursor by-product is 75 mg / L to 130 mg / L.
Citation Information
Patent Citations
Lithium / sodium ion battery positive electrode material production waste liquid recovery, and obtained material and application thereof
CN115594224A
Method for producing nano-battery-grade iron phosphate from titanium white copperas
CN115991463A
Method for preparing sodium ferric sulfate serving as positive electrode material of sodium-ion battery by using titanium dioxide by-product
CN117303449A
Modified sodium ferric sulfate positive electrode material and preparation method thereof, and secondary battery
CN118117067A
Methods of making low cost electrode active materials for secondary batteries from ilmenite
US20150076750A1
